2022
DOI: 10.3390/agronomy12071547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tytanit and Nitrogen on Cellulose and Hemicellulose Content of Festulolium braunii and on Its Digestibility

Abstract: The aim of the experiment was to determine the effects of the foliar application of Tytanit, at the same time comparing it with the effects of mineral nitrogen, on the cellulose and hemicellulose content and its effect on Festulolium braunii digestibility. The experiment was founded in the spring of 2014 in the field of the University of Natural Sciences and Humanities in Siedlce, Poland. The plant used in the experiment was the Felopa variety of Festulolium braunii. The effects of Tytanit foliar application a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Keady [65] reported that N fertilization increases the cellulose and hemicellulose contents in perennial ryegrass. Malinowska and Wiśniewska-Kad żajan [66] also reported an increase in the cellulose content under the fertilization of the Felopa variety of Festulolium brauni (K. Richt.)…”
Section: Chemical Properties Of Grassmentioning
confidence: 89%
“…Keady [65] reported that N fertilization increases the cellulose and hemicellulose contents in perennial ryegrass. Malinowska and Wiśniewska-Kad żajan [66] also reported an increase in the cellulose content under the fertilization of the Felopa variety of Festulolium brauni (K. Richt.)…”
Section: Chemical Properties Of Grassmentioning
confidence: 89%
“…The biostimulant sold under the commercial name of Tytanit contains 8.5 g dm −3 of chelated Ti. Titanium belongs to a group of elements with the lowest phytoaccumulation index, and it stimulates the activity of select enzymes, including catalase, peroxidase, lipoxidase and nitrate reductase [100].…”
Section: Synthetic Biostimulantsmentioning
confidence: 99%
“…According to Malinowska and Wiśniewska-Kad żajan [100], the growth of Festulolium plants is enhanced when N fertilisers are combined with foliar application of Tytanit. In their opinion, Tytanit reduces production costs, delivers environmental benefits and increases the nutritional value of Festulolium plants.…”
Section: Synthetic Biostimulantsmentioning
confidence: 99%
“…Hou et al [21] discussed how sucrose addition can enhance kudzu silage's quality and microbial communities in China. However, Malinowska & Wi'sniewska-Kadzajan [22] recommend using Tytanit combined with nitrogen fertilization for Festulolium braunii cultivation to improve its nutritional value.…”
Section: Overview Of the Simentioning
confidence: 99%